Emerging business transnationalism in Singapore and China: governance, networks, and strategies - Liu, Hong (2023)
Against the backdrop of a rising China and the Fourth Industrial Revolution, there hasbeen increasing interest in the governance models and strategies of ethnic Chinese businesses. Taking this growing literature a step further and seeking to transcend dominant paradigms of businesses and entrepreneurship derived mostly from the Western experiences, this article critically re-evaluates the role of ethnicity and culture in the governance models, behaviour, and networks of transnational Chinese businesses based in Singapore, with operations in Southeast Asia and China. We argue that while ethnicity and culture remain as a significant factor in shaping transnational Chinese business, Chinese companies in Southeast Asia have adopted new corporate governing models and strategies in their engagement with China markets at the time of the Fourth Industrial Revolution. This article adds nuance to the international business and management literature by arguing that the corporate governance, management, and strategies of Chinese companies should not be perceived via a binary perspective, either converging towards or diverging from Western models of businesses and relying solely on ethnicity and culture.